Transformation of the National Army, importance of network analysis in its socialization - Ibarra-Fernández, Mikel I. (EFIM Ediciones, 2021)
Transforming the main pillar of national defense is one of the objectives that the State sets itself and to which it devotes its greatest effort. The main objective of this study is to investigate the transformation process of the national army and to analyze how the communication process is socialized through networks. The methodology used is qualitative, the technique used is documentary analysis. The main conclusion is that network analysis can provide relevant information for the design of transformation socialization plans, such as the identification of the positions with greater centrality and intermediation in the network that is configured with the structure of the Army.